Various Methods to Assess Knee Proprioception - Soni, Jaykumar (Current Practice in Medical Science Vol. 11, 2022)
Proprioception is an important part of motor control that, when impaired or eliminated, can have a significant influence on function in a variety of clinical groups. The purpose of this systematic review was to find clinically relevant techniques for measuring proprioceptive acuity. Proprioception can be elaborated as the sensory feedback contributing to muscle sense, postural equilibrium, and joint stability. The primary goal of this systematic review was to identify and categorise the methods that have been developed and used to measure proprioceptive accuracy. The databases used were PubMed, Scopus, and Web of Science, as well as the following search engines/databases: Cochrane database / SCIRE / PEDro / CINAHL/ EMBASE, and ERIC. The TTDPM technique has lower relative ecological validity but higher conceptual purity. Although JPR tests have lower relative test validity but are more therapeutically viable, the AMEDA approach looks to have better ecological validity as well as relatively higher test and data validity.